Logistics centres development in Latvia - Kabashkin, Igor (Transport, 2007)
In the situation where a large increase in trade and freight transport volumes in the Baltic Sea region (BSR) is expected and in which the BSR is facing a major economic restructuring, efforts to achieve more integrated and sustainable transport and communication links within the BSR are needed. One of these efforts is the development of logistics centres (LCs) and their networking, which will continue to have an impact on improving communication links, spatial planning practices and approaches, logistics chain development and the promotion of sustainable transport modes. These factors will reflect on logistics processes both in major gateway cities and in remote BSR areas. The importance of logistics systems as a whole is not seen clearly enough. Logistics actors see that logistics operations are not appreciated as much as other fields of activity. In addition, logistics centres and the importance of logistics activities to the business life of areas and the employment rate should be brought up better. In the paper main goal and tasks of national approach to LCs development are discussed. Strategic focus of new activities in this area is on the integration of various networks within and between logistics centres in order to improve and develop the quality of logistics networks as well as to spatially widen the networking activities. The key objectives are to integrate the links between logistics centres, ports and other logistics operators in a functional and sustainable way, to promote spatial integration by creating sustainable and integrated approaches to spatial planning of logistics centres and transport infrastructure, to improve ICT‐based networking and communication practices of the fields of transport and logistics and to increase the competence of logistics centres and associated actors by organising educational and training events. The current activities include, for example, the creation of measures for transport networking and port modernisation, multimodal transport network strategies, integrated networks between ports, logistics centres and other operators, the better involvement of LCs in spatial planning and knowledge of the land use needs of the LCs, territorial impact assessments on selected transport corridors where logistics centres are located, the establishment of a common vision of the future spatial and environmental development along the transport corridors and LC‐areas, the elimination of bottlenecks in port‐hinterland‐LC connections, the integration of telematics supported logistics networks based on identification and analysis of networks. First Published Online: 27 Oct 2010